Meta-atoms: From Metamaterials to Metachips - Hao Chi Zhang; Sen Gong; Le Peng Zhang; Yaxin Zhang; Tie Jun Cui (Research)
Electromagnetic (EM) metamaterials represent a cutting-edge field that achieves anomalously macroscopic properties through artificial design and arrangement of microstructure arrays to freely manipulate EM fields and waves in desired ways. The unit cell of a microstructure array is also called a meta-atom, which can construct effective medium parameters that do not exist in traditional materials or are difficult to realize with traditional technologies. By deep integration with digital information, the meta-atom is evolved to a digital meta-atom, leading to the emergence of information metamaterials. Information metamaterials break the inherent barriers between the EM and digital domains, providing a physical platform for controlling EM waves and modulating digital information simultaneously. The concepts of meta-atoms and metamaterials are also introduced to high-frequency integrated circuit designs to address issues that cannot be solved by traditional methods, since lumped-parameter models become unsustainable at microscopic scales. By incorporating several meta-atoms to form a metachip, precise manipulation of the EM field distribution can be achieved at microscopic scales. In this perspective, we summarize the physical connotations and main classifications of meta-atoms and briefly discuss their future development trends. Through this article, we hope to draw more research attention to explore the potential values of meta-atoms, thereby opening up a broader stage for the in-depth development of metamaterials.